Chemical surface analysis on post-thermal treatment of the K-OMS-2 catalysts and catalytic oxidation efficiency at low temperature - Chatkamol Kaewbuddee; Pinit Kidkhunthod; Narong Chanlek; Rattabal Khunphonoi; Kitirote Wantala (Penerbit Universiti Kebangsaan Malaysia, 2019)
The effect of calcination temperature on the physical and chemical properties of cryptomelane (K-OMS-2) was investigated. The K-OMS-2 was synthesized via a hydrothermal method and calcined at 200-600ºC. The catalytic activities of the K-OMS-2 samples were tested in packed bed reactor (PBR) on toluene oxidation. The physical and chemical properties were characterized by X-ray diffractometer (XRD), scanning electron microscopy (SEM), specific surface area computed by Brunauer-Emmett-Teller (BET) equation, Fourier-transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS) and X-ray absorption near edge structure (XANES) techniques. The increasing of the calcination temperature from 200-600ºC led to transform the phases from MnO2 to Mn2O3. The morphology of K-OMS-2 which observed in a nest-like type could promote the catalytic activity. With increasing the calcination temperature, the amount of Oads/Olatt molar ratio slightly increased whereas OH vibrations analyzed by FTIR insignificantly increased. The comparison of interaction effect indicated that the Oads/Olatt molar ratio played an important role in the oxidation performance more than the Mn3+/Mn4+ molar ratio.